PROBLEM OF FORMATION OF THE SYSTEMIC PHILOSOPHY OF THE DOCTOR - T. V. Novikova (Bûlleten' Sibirskoj Mediciny, 2014)
he problem is to translate medical knowledge into the philosophy of the specialist so that he has learned to see mentally not only the thinnest biological structures, but also to feel their displays in scales of a holistic organism. To achieve such effect, special translators are required. For their creation the biomedical knowledge is considered from the viewpoint of sciences about systems: cybernetics, synergetics, nonlinear dynamics, management theory. Examples: model of homeostasis support in terms of the management theory, the adaptation as a series of recombinations of functional systems in the space of compensatory-adaptive reactions, notion of an information resource of adaptive behavior, understanding of structural disorganization of a membrane of the red blood cells as of a universal model of reaction of a holistic organism. For substantiation the possibility to solve the task representation systemic world outlook and systems thinking are introduced, model of self-organization in the system of specialist knowledge and psychology of creative thinking have been involved.